A Descriptive Study Recording and Analyzing the First Language (Arabic) Interference Impact on Arab Learners who Study English as a Second Language (ESL) During Question Formation (London Journal of Research In Humanities and Social Sciences, 2023)
In all hoopla, native language (NL) interference significantly plays an important role in second language disfluency and loss. The current research explores the first language (Arabic) interference impact on Arab students studying English as a second language (ESL) during question structuring. Committed errors categories were noted and analyzed at different linguistic levels. The researcher used a translation test that included ten interrogative sentences to be translated from Arabic into English to determine the learners’ conducted errors during question formation.  The questionnaire consisted of five questions for Arab teachers who teach English as a second language to gain more insight. Participants were randomly selected and included twelve teachers and sixty higher education students who are attending a private college (Medical Lab, Business Management, and Academic writing skills Departments) (N=72, HES=60, LT=12) in the United Arab Emirates. The results showed the deep and severe impact of Arabic as a first language on Arab learners during question formation English in all areas of grammar knowledge.
Keywords: first language; second language; impact; interference